Structural modulation, oriented growth of rock salt, and spinel in (Co(Cr/Mg)FeMnNi) multicomponent oxide and derivatives - Mukherjee S.; Mukhopadhyay N.K.; Basu J. (My University, 2025)
Phases, interfaces, microstructure, and stabilization mechanism in multicomponent (Co(Cr/Mg)FeMnNi)-oxide along with its binary, ternary, and quaternary derivatives, synthesized through solid-state route, have been studied by X-ray diffraction and transmission electron microscopy. Formation of single-phase spinel in multicomponent (CoFeMgMnNi)-oxide after sintering at 1473 K for 10 h is being reported with preferential growth of rock salt phase upon longer holding time. Oriented growth of spinel with rock salt and formation of coherent/semi-coherent interface structure helps in minimizing the interface strain. Equimolar ternary derivative, (CoMgNi)-oxide, after sintering at 1473 K for 10 h forms a rock salt phase along with a minor volume fraction of spinel phase. Ternary (CoMgNi)-oxide and multicomponent (CoFeMgMnNi)-oxide, upon prolonged sintering or aging, develop structural modulation with/without chemical partitioning that is evident from the electron diffraction patterns through spot splitting, intensity modulation, and arcing. Single-phase spinel forming (CoCrFeMnNi)-multicomponent oxide develops structurally modulated microstructure upon sintering and quenching, which is being observed for the first time. Stabilization of the multicomponent oxides is explained as a trade-off between the high configurational entropy due to the presence of multiple cations in the cation sublattice and the minimization of strain energy in the crystal of the multicomponent oxide. © 2025 The American Ceramic Society.